The Latest Datable Cuneiform Tablets - Sachs, A.
copies D. T. 143, BM 45982 = SH. 81-7 6,425, BM. 40084 = 81-2-1,49, Dropsie College text; 5 pl.; photos of same texts, also Metropolitan Museum 86.11.354 and BM. 40083 = 81-2-1,48.